Quantitative Research on Gen Z Slang Terms for a Diverse Group of People - S. Shruthi; B. R. Aravind; M.L. Mathivysali (Emerging Trends in Languages, 2024)
This study objective is to determine the various individuals who employed vocabulary connected with Generation Z and to discover who those persons were. Through the use of Google forms, twenty Gen Z slang terms associated were posed to the various participants for testing. The data are collected from the participants by the researcher through the use of Google Forms, and the researcher is the one who is responsible for developing the question that is being asked. In this study, a wide range of subjects were included. The inquiry was carried out utilizing a quantitative methodology, and the findings were presented to the audience. The goal of this study required the participation of forty people who ranged in different age group and came from a variety of different backgrounds. As a result of the data, it is evident that a significant number of individuals do not use language that is associated with the generation of Gen Z while they are having conversations. The slang of Generation Z is made up of a very limited number of terms, the bulk of which are hidden and have not yet been used by the general public for widespread use. It is also proposed that the various generations' slang phrases are not widely known by a large number of people; consequently, in addition, it is recommended that future study might concentrate on the terms that are linked with those generations. Given the limited number of participants, more investigations might be conducted to validate the findings with huge participants.
Keywords: Gen Z; Learning Awareness; Mobile Usage; Slang Words; Verbal Communication